Circular product design: strategies, challenges and relationships with new product development - Aguiar, Marina Fernandes [UNESP]; Mesa, Jaime A.; Jugend, Daniel [UNESP]; Pinheiro, Marco Antonio Paula [UNESP]; Fiorini, Paula De Camargo (Emerald, 2022)
Purpose: Although product design is a fundamental element in the transition towards the circular economy, the knowledge of practices, methods and tools oriented to circular product design has not been widely developed. This study aims to contribute to the circular economy research area by investigating and analyzing the main design approaches to circular products and their relationship to new product development. Design/methodology/approach: The authors conducted a systematic review and qualitative analysis of 120 articles. In these studies, the authors analyzed aspects such as design strategies used, the barriers to the adoption of circular product design and the relationships between the phases of new product development processes with circular product design studies. Findings: The findings revealed that the circular product design approach has added new design strategies to those already recommended by ecodesign, such as multiple use cycles, emotional durability and biomimicry. Furthermore, the results showed that most circular product design articles focus on the planning and concept development phases of the new product development process. Originality/value: In this article, the authors systematized the findings of an emergent research area: the development of new products for the circular economy. Its main contributions lie in the identification of design strategies, the classification of Design for X approaches, analysis of such approaches during the new product development process and discussion of their main barriers. Finally, this study presents contributions for managers and designers who are starting the transition to a circular strategy.
Keywords: Circular economy; Ecodesign; Framework; Management; Sustainability